Analisis Kesehatan Finansial Mahasiswa Tasikmalaya Finansial Stres dan Gaya Hidup - risky ridwansyah; Iman Fauzi Sudirman; han han burhani (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
This study aims to analyze the effect of financial stress and lifestyle on students’ financial health in Tasikmalaya. The research employs a quantitative approach using a survey method, with data collected through questionnaires distributed to students as respondents. The data were analyzed using multiple linear regression with the support of statistical software, including validity, reliability, classical assumption, and hypothesis testing. The results indicate that financial stress and lifestyle have a positive and significant effect on students’ financial health, both partially and simultaneously. These findings suggest that financial pressure and lifestyle patterns play an important role in determining the level of financial health among students. Therefore, effective financial stress management and lifestyle control are essential in improving students’ financial well-being.